The Translation Result Evaluation Of Non-Standard English Simple Sentences (African American Vernacular English) Into Indonesian In The Novel Entitled The Help By Kathryn Stockett - Doni Anggoro Ari Santoso (Scope : Journal of English Language Teaching, 2019)
AbstrakThis research is an overall view over translation of African American Vernacular English (AAVE) especially simple sentences in the novel The Help by an American author Kathryn Stockett and in the translation by Barokah Ruziati. The writer chooses this topic and the novel as main sources that are analyzed because she realizes that the use of Non-Standard English particularly AAVE is rarely used in writing novels in general.The objectives of this research are: (1) to analyze the translation of simple sentences   from   Non-Standard   English   into   simple   sentences   from   Standard Indonesian; (2) and to analyze the result that accordance with a good criteria of translation.This novel is written in Non-Standard English particularly AAVE and it is translated into Standard  Indonesian.  The writer analyzes simple sentences in the novel to figure out the quality of its translation.To analyze this novel the writer uses descriptive    qualitative    method.    The writer analyzes descriptive data in form sentences, in specific are simple sentences that are taken from the novel. From this research it can be conclude that there is63.29% of accurate translation and 36.70% of less accurate translation.